Collector vs. taxpayer: The game of tax evasion - Lara Pulido, José Alberto (Estudios Económicos de El Colegio de México, 2007)
This paper incorporates the strategic interactions between tax payers and fiscal authorities to the standard theory of fiscal evasion. The existence and (local) unicity of Nash equilibrium are demonstrated by the players’ best responses. Through a numerical analysis, it is concluded that “greater sanctions, the establishment of fiscal discipline, the improvement of monitoring processes and less corruption, reduce fiscal evasion”. Finally, it is established that, if sufficiently deep, progressiveness on the tax system has a beneficial impact in collection, and that economic growth provokes both, a reduction in evasion and the improvement of social welfare.